Innovative pitcher-shaped antenna with dual notches on a flexible leather substrate for c-band communication - Anurag Saxena; Raghav Agarwal; Vinod Kumar Singh; Ramesh Kumar Verma; Ratnesh Tiwari (Discover Electronics)
Abstract This article presents a circularly polarized (CP) flexible antenna in the shape of a pitcher that is suited for use in C-band (4 to 8 GHz) applications. The C-band has a wavelength that ranges from 7.5 to 3.75 cm as stated by the IEEE frequency spectrum. In terms of design, the wearable antenna is straightforward and was fashioned after the texture of leather. There is a pitcher-shaped radiating element which is designed with a defective ground. The process known as microstrip linefeed is utilized in order to provide the power in antenna. The impedance bandwidth of the proposed antenna is observed to be 20.35% (1.36 GHz) ranging from 6 to 7.36 GHz. The reflection coefficient at the resonant frequency of 6.704 GHz is rather remarkable and was observed to be − 30 dB. However, the axial ratio bandwidth of the proposed antenna is observed to be 13.74% (900 MHz) ranging from 6.1 to 7 GHz. The utilization of a parametric report serves to provide justification for the appropriateness of the projected antenna. In order to determine whether or not the newly presented antenna is feasible, it is produced and put through a series of tests using a vector network analyzer. A significant amount of comprehension was discovered through the examination of the recreated and estimated findings. The maximum gain achievable with the suggested antenna is 4.67 dBi. The proposed antenna also provides more than 75% efficiency in resonating band.